2014
DOI: 10.1007/jhep03(2014)119
|View full text |Cite
|
Sign up to set email alerts
|

Jet veto clustering logarithms beyond leading order

Abstract: Many experimental analyses separate events into exclusive jet bins, using a jet algorithm to cluster the final state and then veto on jets. Jet clustering induces logarithmic dependence on the jet radius R in the cross section for exclusive jet bins, a dependence that is poorly controlled due to the non-global nature of the clustering. At jet radii of experimental interest, the leading order (LO) clustering effects are numerically significant, but the higher order effects are currently unknown. We rectify this… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 67 publications
0
24
1
Order By: Relevance
“…[25]. At first sight it appears to disagree with our analytical result and after consultation with the authors they identified an issue in their treatment of R-dependent running coupling-related terms.…”
Section: Jhep04(2015)039contrasting
confidence: 71%
See 1 more Smart Citation
“…[25]. At first sight it appears to disagree with our analytical result and after consultation with the authors they identified an issue in their treatment of R-dependent running coupling-related terms.…”
Section: Jhep04(2015)039contrasting
confidence: 71%
“…However, given the initial disagreement with the results of [25], such cross-checks became desirable. In principle one could take a program such as MCFM and directly take the limit of small p t and small R in the Higgs plus two jet process at NLO, in order to directly cross-check the C the test as shown in figure 10 is in some respects more complete because it probes the f hardest (z) distribution differentially.…”
Section: B2 Fixed-order Cross Checksmentioning
confidence: 99%
“…A systematic study on the jet veto clustering effects up to O(α 3 s ) in the small-jet-radius limit was carried out in ref. [30].…”
Section: Jhep06(2014)028mentioning
confidence: 99%
“…(C.1), with tabulated coefficients for n f = 4, 5 in table 7 (the second order coefficient was also calculated in ref. [37]). The quantity t(R 0 , R, p t ) is an integral of the coupling over scales related to the allowed emission angles, defined specifically as…”
Section: Jhep04(2016)049mentioning
confidence: 99%